Discourse in late modernity : rethinking critical discourse analysis - Chouliaraki, Lilie (Critical discourse analysis series., 1999)
"Discourse in Late Modernity sets out to show that critical discourse analysis is strongly positioned to address empirical research and theory-building across the social sciences, particularly research and theory on the semiotic/linguistic aspects of the social world. It situates critical discourse analysis as a form of critical social research in relation to diverse theories from the philosophy of science to social theory and from political science to sociology and linguistics."--Jacket